Impact of a soft tip nicotine-free harmless cigarette as part of a smoking cessation program with psychological support and varenicline: an integrated workplace smoking cessation intervention - Marilena Maglia; Pasquale Caponnetto; Riccardo Polosa; Cristina Russo; Giuseppe Santisi (Health Psychology Research)
Cigarette consumption in the general population has shown a sustained decline over the past 20 years, but despite this, it is essential to monitor consumption among smokers at their workplace. There is an association between cigarette addiction and work-related stressors, with high prevalence rates for smokers, at least double those of other adults. This two-group randomized clinical trial compared the 12-week combined effect of psychological support and varenicline associated with the use or not of a nicotine-free inhaler with a soft mouthpiece (QuitGo™) on the 4 to 24-week cessation rate in enrolled smokers to a smoking cessation program promoted by our research group. The results of the logistic model analysis showed that the likelihood of quitting successfully at week 24 was significantly higher in the QuitGO™ group than in the control group for participants with high behavioral dependence as assessed by Glover-Nilsson Smoking Behavioral Questionnaire-GN-SBQ (OR = 8.55; CI at 95% = 1.75-43.20). The data presented suggest that the soft tip nicotine-free harmless cigarette may be helpful for smokers and those with work-related stress symptoms who recognize the need to have a gesture in the traditional cigarette smoking ritual.